Firm adjustment to trade policy changes in East Asia - Dionisius Narjoko; Shujiro Urata (Asian Development Bank Institute (ADBI), 2019)
Trade and investment liberalization has been one of the key features of economic policy in many developing countries since the 1990s. Research on this subject has consistently produced more evidence on the benefits of globalization; theoretical studies give more attention to what happens within an industry when trade and liberalization occur, while empirical studies confirm the positive impact of trade liberalization. This paper reviews some recent studies on the subject of firms in a globalized economy to enable us to understand more about how firms respond to globalization or changes in trade and investment liberalization. The paper focuses on presenting or explaining the underlying mechanisms through which the effects are realized. The studies summarized in this paper generally confirm the positive impact of trade liberalization on productivity or the spectrum of measures reflecting productivity, such as product quality, firm size, or skill intensity. The positive impact goes through various channels, including competition and industry dynamics, exporting and innovation decisions, and production or investment decisions.
Keywords: F1; F6; O14; O53; 330; trade liberalization; investment liberalization; globalization; productivity